Evaluation of the listening comfort in pedagogical environments at the catholic university of Manizales, Colombia (2019)
The listening comfort is an element that affects people’s health and their quality of life. The listening comfort may or may not benefit the teaching and learning processes. For that reason, this research shows the studies done regarding ambient noise and time of reverberation in the basic pedagogical internal environments located at the Catholic University of Manizales, which have been classified and analyzed according to the Colombian regulation NTC 4595 for the planning and design of facilities and educational settings. There have been studied twenty-two areas, which represent the general acoustic conditions in the campus. The results showed a compliance rate of 5% in both ambient noise and reverberation time, proving the need to implement policies and guidelines to improve soundproofing and acoustic conditioning, towards generate optimal learning spaces.